An Overlooked Manifestation of Hypercortisolism-Cerebral Cortical Atrophy and Challenges in Identifying the Etiology of Hypercortisolism: A Report of 2 Pediatric Cases - GÜRAN, TÜLAY (My University, 2023)
Introduction: Endogenous Cushing\"s syndrome (CS) is a rare, severe disease that can cause multiple systemic involvement and behavioral problems due to excessive cortisol production. Structural changes can be noted in the brain magnetic resonance imaging (MRI) scans of these cases. Cases: A 9-year-old girl and a 13-year-old boy were admitted with hypercortisolism. In the female patient, altered consciousness was prominent along with cerebral and cerebellar brain atrophy, and findings indicating posterior reversible encephalopathy syndrome were detected in the brain MRI. Although the male patient\"s neurological examination was normal, significant cerebral atrophy was seen in the brain MRI. Case 1 was diagnosed as having ectopic ACTH syndrome (EAS) due to a thymic carcinoid tumor. Case 2 underwent a pulmonary lobectomy upon detection of a bronchial lesion in the Ga-68 DOTATATE PET/CT scan while being examined for EAS due to a lack of suppression in the high-dose dexamethasone suppression test. However, hypercortisolism persisted despite the removal of the bronchial lesion, and subsequently, a diagnosis of Cushing\"s disease was established following bilateral inferior petrosal sinus sampling.Discussion: Endogenous hypercortisolism may cause brain atrophy of varying severity. Central nervous system findings can be overlooked in children with CS. More comprehensive studies are needed to better understand the behavioral changes caused by the effects on the brain and to evaluate whether these changes are reversible. In addition, identifying the source of hypercortisolism can be difficult due to a lack of experience related to the rarity of the disease in children.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Internal Diseases; Endocrinology and Metabolic Diseases; Health Sciences; ENDOKRİNOLOJİ VE METABOLİZMA; Klinik Tıp; Klinik Tıp (MED); PEDİATRİ; ENDOCRINOLOGY & METABOLISM; CLINICAL MEDICINE; Clinical Medicine (MED); PEDIATRICS; Pediatri; Endokrin ve Otonom Sistemler; Pediatri, Perinatoloji ve Çocuk Sağlığı; Endokrinoloji, Diyabet ve Metabolizma; Endokrinoloji; Yaşam Bilimleri; Pediatrics; Endocrine and Autonomic Systems; Pediatrics, Perinatology and Child Health; Endocrinology, Diabetes and Metabolism; Endocrinology; Life Sciences